UTILIZATION OF LIQUID WASTE SEDIMENT LEATHER INDUSTRI FOR CHILLI PLANTS FERTILIZER - Sofwan Siddiq Abdullah (Politek ATK Yogyakarta Press, 2022)
The purpose of this study was to utilize solid waste from wastewater treatment sludge for red chili fertilizer by finding the proportion/ratio of solid waste components with soil to obtain the most optimal composition. The materials used are solid waste sediment leather tannery, soil, chili seedlings, pesticides, and water. The tools used are plant pots (pots made of clay with a diameter of ± 25 cm and a height of ± 20 cm). The method used was planting red chili seeds on 6 types of planting media, namely control pots, 1,2,3,4,5 pot which were sequentially controlled (without solid waste), and the ratio of solid waste: soil with a ratio of 1:2, 1: 3, 1:4, 1:5, 1:6. The results of the data obtained were analyzed using a T test and completely random design. furthermore, duncan test was conducted to determine the best dose (ratio) for chili plants if previously (in the unidirectional variance test) there was a ratio effect. The results obtained were pots 1, 2, 4 had a higher plant height than the control. Pots 1,2,3,4 had more leaves than the control. The conclusion that can be obtained is that the solid waste sediment on chili planting media affects height increase, number of chili leaves, and quantitatively not all of them have a significant effect. Giving solid waste sediments with a ratio of 1: 3 showed the fastest increase in height and number of leaves.